2018
DOI: 10.1021/acs.est.8b03219
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Risk Assessment of Atmospheric PM2.5 and PM10 Particulate-Bound PAHs and NPAHs in Rwanda, Central-East Africa

Abstract: Exposure to airborne particulates is estimated as the largest cause of premature human mortality worldwide and is of particular concern in sub-Saharan Africa where emissions are high and data are lacking. Particulate matter (PM) contains several toxic organic species including polycyclic aromatic hydrocarbons (PAHs) and nitrated PAHs (NPAHs). This study provides the first characterization and source identification for PM10- and PM2.5-bound PAHs and NPAHs in sub-Saharan Africa during a three-month period that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 61 publications
3
55
0
Order By: Relevance
“…The majority of studies reviewed in this study found that the mean concentrations of atmospheric PM 2.5 and PM 10 in Africa greatly exceeded the 2006 WHO guideline value of annual and 24-h mean, and those carcinogenic and mutagenic organic pollutants are a major component of PM (Figure 2). Despite available publications of atmospheric NPAHs in Rwanda [34], Egypt [116], and Algeria [117] (Figure 3), the atmospheric concentrations of total PAHs and NPAHs show a large variation among these countries. The PAH concentrations, in descending order, were Senegal, Kenya, South Africa, Mali, Uganda, Rwanda, Sierra Leone, Algeria, and Egypt.…”
Section: Chemical Composition Of Ambient Particulate Matter In Africamentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of studies reviewed in this study found that the mean concentrations of atmospheric PM 2.5 and PM 10 in Africa greatly exceeded the 2006 WHO guideline value of annual and 24-h mean, and those carcinogenic and mutagenic organic pollutants are a major component of PM (Figure 2). Despite available publications of atmospheric NPAHs in Rwanda [34], Egypt [116], and Algeria [117] (Figure 3), the atmospheric concentrations of total PAHs and NPAHs show a large variation among these countries. The PAH concentrations, in descending order, were Senegal, Kenya, South Africa, Mali, Uganda, Rwanda, Sierra Leone, Algeria, and Egypt.…”
Section: Chemical Composition Of Ambient Particulate Matter In Africamentioning
confidence: 99%
“…African automobile emissions (Diesel and gasoline) and biomass burning were considered major contributors of PAHs and NPAHs in urban and rural sites, respectively (Table 2). The [1-NP]/[Pyr] ratios in Kigali, Rwanda were 0.05 (dry season) and 0.04 (wet season) [34], while the values in the Great Cairo Area, Egypt were 0.06 (winter) and 0.03 (summer) [116]. The values in these two African countries were similar to those reported in East Asian cities influenced by large volumes of vehicle emissions [82].…”
Section: Chemical Composition Of Ambient Particulate Matter In Africamentioning
confidence: 99%
See 3 more Smart Citations